2015
DOI: 10.12934/jkpmhn.2015.24.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perceived Parenting Styles on Depression and Smartphone Addition in College Students

Abstract: Purpose:The purposes of this study were to examine differences in depression and smartphone addiction among four styles of perceived parenting, and determine whether the perceptions of paternal and maternal parenting are associated with depression and smartphone addiction among college students. Methods: A cross-sectional descriptive correlational design was used. A convenience sample of 378 undergraduate students responded to the survey. Data were analyzed using ANOVA, Pearson correlation, and multiple regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
4
10
1
Order By: Relevance
“…The finding is consistent with prior extended parenting literature, e.g., scholars have linked parental worry (or parental warmth) with poor well-being (Parker, 1983) and development of compulsive behaviors (Zlomke & Young, 2009). Similarly, prior literature on the Internet and social media use have also shown that parental worry was positively correlated with compulsive ICT use and negative well-being (Dogan, Bozgeyikli, & Bozdas, 2015;Yoo & Kim, 2015;Zhang et al, 2015). The possible reason could be that, on experiencing parental worry, young people tend to cope with this parental pressure by seeking stimulation through social media use which results in social media fatigue.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The finding is consistent with prior extended parenting literature, e.g., scholars have linked parental worry (or parental warmth) with poor well-being (Parker, 1983) and development of compulsive behaviors (Zlomke & Young, 2009). Similarly, prior literature on the Internet and social media use have also shown that parental worry was positively correlated with compulsive ICT use and negative well-being (Dogan, Bozgeyikli, & Bozdas, 2015;Yoo & Kim, 2015;Zhang et al, 2015). The possible reason could be that, on experiencing parental worry, young people tend to cope with this parental pressure by seeking stimulation through social media use which results in social media fatigue.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are inconsistent with prior extended literature on parental mediation strategies, e.g., parental monitoring is useful in shielding young people from engaging in compulsive ICT use (e.g., Eijnden et al, 2010) and online risky behavior (Patterson & Stouthamer-Loeber, 1984); and parental permission was positively associated with CIU (Zhang et al, 2015). Although there were also relatively recent studies showing that parental monitoring is positively correlated with compulsive ICT use (Eijnden et al, 2010;Yoo & Kim, 2015), our research found that, in terms of SNS or MIM fatigue, parental monitoring and permission play little role and would not be considered as effective strategies to reduce adolescents' fatigue.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…났다 (Choi & Kim, 2013;Yoo & Kim, 2015). (Kim, 2013;Choi, 2013 (Na, 2013;Lee, 2014;Kwon, 2013;Jung & Kim, 2014).…”
Section: 성을 경험이 스마트폰 중독에 영향을 미치는 것으로 나타mentioning
confidence: 99%